Preparation method of lithium lanthanum powder with micro-nano structure and its application in lithium metal battery

The preparation of lithium lanthanum powder with micro-nano structure through the frozen ball milling process solves the problems of dendrites growth and volume changes during the charging and discharge process of lithium metal batteries, and improves the safety and stability of the battery, extends the cycle life and increases the energy density.

CN118437919BActive Publication Date: 2025-04-18XIAN TECH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410524437.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-29
Publication Date
2025-04-18
Estimated Expiration
2044-04-29

AI Technical Summary

Technical Problem

During the charging and discharging process, existing lithium metal batteries have Li+ deposition/stripping leading to dendrite growth and volume changes, resulting in low Coulomb efficiency, poor circulation and rate performance, and even safety hazards such as fire/explosion may occur.

Method used

Lithanum powder with micro-nano structure was prepared by frozen ball milling process, and the lithium powder was modified by paraxylene as a dispersant, polymethyl methacrylate (PMMA) and octadecylphosphonic acid as a protective agent to form fine-grained lithium lanthanum powder.

Benefits of technology

The preparation process is simplified, the preparation efficiency of lithium powder is improved, the local current density of the electrode is reduced, the growth and volume expansion of dendrites are suppressed, the safety and stability of lithium metal batteries are improved, the cycle life of the battery is extended, and the energy density is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118437919B_ABST
    Figure CN118437919B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing lithium lanthanum powder with a micro-nano structure and its application in lithium metal batteries. The method comprises: step one, weighing metallic lithium and lanthanum, polymethyl methacrylate (PMMA), octadecylphosphonic acid and p-xylene with an electronic balance; step two, putting the weighed raw materials into a frozen ball mill, and using frozen ball milling to pulverize them at ‑196°C, which appear as very fine nanoparticles at the microscopic scale. The powdered lithium metal prepared by the present invention has an advantage in specific surface area, and can greatly reduce the local current density of the electrode, thereby reducing the polarization of the lithium anode and improving stability. The lithium lanthanum powder prepared by this method improves the safety and stability of lithium metal batteries. The prepared samples were assembled into a Li-La alloy||Li-La alloy symmetrical battery for electrochemical performance testing, and the critical current density value reached 63 mA cm ‑2 , at 1 mA cm ‑2 , 1 mAh cm ‑2 Under the conditions of , the battery can stably cycle for 2200 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention belongs to the technical field of new energy materials and preparation thereof, and specifically relates to a method for preparing lithium lanthanum powder with a micro-nano structure and application thereof in lithium metal batteries. Background technology:

[0002] At present, rechargeable lithium-ion batteries (LI B) have become the mainstream choice in the fields of electronic products, energy storage and electric vehicles. Metal lithium batteries are known as the "holy grail" of lithium-ion batteries, with high theoretical specific capacity (3860mAh g -1 ) and low redox potential (-3.04V vs. standard hydrogen electrode) of lithium metal anode have attracted much attention and are considered to be ideal candidates for lithium battery anode materials. Although Li-S and Li-O2 batteries have significant advantages in energy density, their practical applications rely heavily on the electrochemical reversibility and safety of lithium metal anodes. While pursuing higher energy density, ensuring the stability and safety of lithium metal anodes has become the key to the development of these battery technologies. However, the application of lithium metal anodes in rechargeable batteries faces major technical challenges, mainly due to the fact that Li metal anodes are not easily reversible during the charging and discharging process of the battery. + Deposition / stripping leads to dendrite growth and large volume change, as well as side reactions with the electrolyte, which in turn cause low Coulombic efficiency (CE), poor cycling and rate performance, and even potential safety hazards such as fire / explosion.

[0003] To solve the above problems, researchers have developed a variety of modification strategies, including current collector modification, construction of a stable solid electrolyte interface (SEI), construction of composite electrodes, etc. At present, the preparation of lithium metal powder mainly adopts melt dispersion and droplet emulsification technology. The following is a specific analysis:

[0004] The document with the announcement number "CN 105762328 B" discloses a "method for preparing passivated lithium powder", which includes the following steps: (1) adding metallic lithium to a first solvent under an inert atmosphere, wherein the first solvent does not react with metallic lithium, heating until the metallic lithium is melted, stirring to disperse the molten metallic lithium, and washing and drying after cooling to obtain lithium powder particles. (2) adding a metal salt to a second solvent under an inert atmosphere to obtain a solution, wherein the second solvent does not react with metallic lithium, adding the lithium powder particles obtained in step (1) to the solution, and the lithium powder particles and the metal salt undergo an in-situ reduction reaction, coating the surface of the lithium powder particles with a metal layer, and washing and drying the reaction product to obtain passivated lithium powder. The existing problems are: the preparation process is complicated; the lithium metal needs to be stirred and heated at high speed; and the need to stir the lithium powder and the solvent leads to low efficiency, which limits its wide application. Summary of the invention:

[0005] The present invention aims to provide a method for preparing lithium lanthanum powder with micro-nano structure and its application in lithium metal batteries, so as to solve the problems of complex preparation, high energy consumption and low lithium powder preparation efficiency existing in the prior art.

[0006] To achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing lithium lanthanum powder with micro-nano structure comprises the following steps:

[0007] Step 1: weigh metallic lithium and lanthanum with an atomic ratio of 99:1 using an electronic balance, then weigh 15-20% of polymethyl methacrylate (PMMA) and 0.1-0.3% of octadecylphosphonic acid, and add 2-3 mL of p-xylene to every 1000 mg of metallic lithium and lanthanum;

[0008] Step 2: Put the weighed raw materials into a frozen ball mill with a ball-to-material ratio of 100:1-200:1. Use a frozen ball mill, pre-freeze for 10-20 minutes, work at an alternating frequency of 25-30 Hz for 5-6 minutes and 3-7 Hz for 2-3 minutes, and go through 7-9 cycles to obtain lithium lanthanum powder with a micro-nano structure.

[0009] Furthermore, in the above step 1, polymethyl methacrylate accounts for 15% of the total mass of metallic lithium and lanthanum, octadecyl phosphoric acid accounts for 0.2%, and 2 ml of p-xylene is added to every 1000 mg of metallic lithium and lanthanum.

[0010] Furthermore, the above method also includes step three, sieving the lithium lanthanum powder using a 150-250 mesh sieve.

[0011] Furthermore, in the above step 2, the weighed raw materials are placed in a frozen ball mill with a ball-to-material ratio of 100:1, and a frozen ball mill is used. After pre-freezing for 15 minutes, the raw materials are operated at an alternating frequency of 30 Hz for 5 minutes and 5 Hz for 2 minutes, for 7 cycles.

[0012] The above-mentioned application of lithium lanthanum powder with micro-nano structure in lithium metal batteries.

[0013] The above-mentioned application of lithium lanthanum powder with micro-nano structure in lithium metal battery is to use 300-500 mesh 316L stainless steel mesh screen with a diameter of 8-12mm to sieve the lithium lanthanum powder and then load it on the stainless steel mesh screen to prepare an electrode sheet.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] 1. In the preparation process of the present invention, p-xylene is used as a dispersant, methyl methacrylate (PMMA) and octadecylphosphonic acid are used to protect and modify lithium powder, and then frozen ball milling is performed, so that active metals such as lithium metal are prepared into nano-level lithium powder in this way. This method can not only avoid dependence on high temperature environment, but also simplify the preparation process. Since the preparation process is simple, it can be prepared in large quantities, thereby improving the preparation efficiency of lithium powder. In this process, PMMA and octadecylphosphonic acid are used as protective agents, and p-xylene is used as a dispersant to play a key role, which is conducive to the formation of fine particles and the collection and processing of the final product. The powdered lithium metal prepared by the present invention has advantages in specific surface area, can greatly reduce the local current density of the electrode, thereby reducing the polarization of the lithium anode, and the volume expansion of the lithium metal anode is more effectively controlled, so that the electrode can be in a quasi-equilibrium state during the reaction process, inhibiting dendrite growth and volume expansion, and improving stability. The lithium powder prepared by this method improves the safety and stability of lithium metal batteries. At the same time, the present invention adopts a cryo-ball milling process for subsequent preparation. From the scanning electron microscope image, it can be seen that the lithium metal particles are covered with PMMA and octadecylphosphonic acid at 3 μm. The microstructural characteristics show the effectiveness of the cryo-ball milling process for constructing this micro-nano structure. This micro-nano structure provides a large specific surface area and improves the overall mechanical strength and stability of the electrode material.

[0016] 2. Due to the strong compatibility between lanthanum metal elements and lithium, the present invention introduces lanthanum as a composite raw material, mixes it with lithium powder, and then uses a freezing ball milling process to prepare lithium lanthanum powder. The battery prepared in this way is more stable and reliable during the cycle process. This stability not only extends the cycle life of the battery, but also improves its energy density and charging efficiency. The prepared lithium lanthanum powder was assembled into a Li-La alloy||Li-La alloy symmetrical battery for electrochemical performance testing. The impedance spectrum (EIS) showed that the charge transfer resistance was about 11Ω and the CCD value was 63mA cm -2 At 1mA cm -2 , 1mAh cm -2 Under the conditions of , the battery can stably cycle for 2200 hours.

[0017] 3. Wide application scope: The material of the present invention can be applied to positive electrode pre-lithiation and is widely used in electric vehicles, energy storage systems, portable electronic devices and other fields. Description of the drawings:

[0018] Figure 1 This is the SEM image of lithium-lanthanum alloy (Li-La at% = 99:1);

[0019] Figure 2 This is the EDS diagram of lithium lanthanum alloy (Li-La at% = 99:1);

[0020] Figure 3 XRD spectrum of lithium lanthanum alloy (Li-La at% = 99:1);

[0021] Figure 4 EIS diagram of a symmetric battery assembled with lithium-lanthanum alloy (Li-La at% = 99:1);

[0022] Figure 5 The critical current density (CCD) diagram of a symmetric battery assembled with lithium-lanthanum alloy (Li-La at% = 99:1);

[0023] Figure 6 The symmetric battery assembled from lithium-lanthanum alloy (Li-La at% = 99:1) has a high conductivity at 1 mA cm -2 , 1mAh cm -2 Cycling performance under conditions;

[0024] Figure 7 :A symmetric battery assembled from lithium-lanthanum alloy (Li-La at% = 99:1) at 3 mA cm -2 , 1mAh cm -2 Cycling performance under . Specific implementation method:

[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments and drawings.

[0026] Embodiment 1: A method for preparing lithium lanthanum powder with micro-nano structure, comprising the following steps:

[0027] Step 1: Use an electronic balance to weigh 870 mg of metallic lithium and 220 mg of lanthanum as raw materials, heat and mix at 250° C., then weigh 163.5 mg of polymethyl methacrylate (PMMA), 2.6 mg of octadecylphosphonic acid, and 2.5 ml of p-xylene;

[0028] Step 2: Put the weighed raw materials into a frozen ball mill with a ball-to-material ratio of 100:1. Use a frozen ball mill, pre-freeze for 15 minutes, and then work at -196°C at an alternating frequency of 30 Hz for 5 minutes and 5 Hz for 2 minutes for 7 cycles.

[0029] Step 3: Take out the sample and filter it using a 200-mesh sieve to obtain lithium lanthanum powder with a micro-nano structure.

[0030] Example 2: A method for preparing a lithium lanthanum powder negative electrode material with a micro-nano structure, comprising the following steps:

[0031] Step 1: Use an electronic balance to weigh 870 mg of metallic lithium and 220 mg of lanthanum as raw materials, and then weigh 200 mg of polymethyl methacrylate (PMMA), 1 mg of octadecylphosphonic acid, and 2 ml of p-xylene;

[0032] Step 2: Put the weighed raw materials into a frozen ball mill with a ball-to-material ratio of 200:1. Use a frozen ball mill. After pre-freezing for 15 minutes, work at an alternating frequency of 28 Hz for 5 minutes and 4 Hz for 3 minutes, and go through 8 cycles.

[0033] Step 3: Take out the sample and filter it using a 250-mesh sieve to obtain lithium lanthanum powder with a micro-nano structure.

[0034] Embodiment 3: A method for preparing a lithium lanthanum powder negative electrode material with a micro-nano structure, comprising the following steps:

[0035] Step 1: Use an electronic balance to weigh 870 mg of metallic lithium and 220 mg of lanthanum as raw materials, and then weigh 150 mg of polymethyl methacrylate (PMMA), 3 mg of octadecylphosphonic acid, and 3 mL of p-xylene;

[0036] Step 2: Put the weighed raw materials into a frozen ball mill with a ball-to-material ratio of 150:1. Use a frozen ball mill. After pre-freezing for 18 minutes, work at an alternating frequency of 30 Hz for 6 minutes and 6 Hz for 2 minutes. After 9 cycles, take out the sample to obtain lithium lanthanum powder with a micro-nano structure.

[0037] The above-mentioned Example 1 is the best example. The lithium lanthanum powder with micro-nano structure obtained in Example 1 was loaded on a stainless steel grid after being sieved through a 316L stainless steel mesh with a diameter of 10 mm and a mesh size of 400 to prepare an electrode sheet, and the product was tested:

[0038] At 3 μm, lithium metal particles were shown to be coated with PMMA and octadecylphosphonic acid (see Figure 1 ), this micro-nano structure provides a large specific surface area, improving the overall mechanical strength and stability of the electrode material. The microstructural characteristics show the effectiveness of the cryo-milling process for constructing this micro-nano structure.

[0039] See Figure 2 ,The EDS element mapping diagram clearly shows the uniformity of element distribution in the micro-nano structure, further illustrating the consistency of lithium lanthanum element distribution in the entire electrode material.

[0040] See Figure 3 No other clear phases were observed in the physical phase of the prepared samples.

[0041] See Figure 4The samples were assembled into symmetrical batteries to test the electrochemical performance, and the electrochemical impedance spectroscopy (EIS) showed that the charge transfer resistance was about 11Ω.

[0042] See Figure 5 , the critical current density is as high as 63mA cm -2 .

[0043] See Figure 6 , at 1mA cm -2 , 1mAh cm -2 Under the conditions of , the battery can stably cycle for 2200 hours.

[0044] See Figure 7 , at 3 mA cm -2 , 1mAh cm -2 Under the condition of , it can circulate for 2100h.

[0045] The above description is only a preferred embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing lithium lanthanum powder with micro-nano structure, characterized in that: The following steps are included Step 1: weigh metallic lithium and lanthanum with an atomic ratio of 99:1 using an electronic balance, then weigh 15-20% of the total mass of metallic lithium and lanthanum polymethyl methacrylate (PMMA), 0.1-0.3% of octadecylphosphonic acid, and add 2-3 mL of p-xylene to every 1000 mg of metallic lithium and lanthanum; Step 2: Place the weighed raw materials into a frozen ball mill with a ball-to-material ratio of 100:1-200:

1. Use a frozen ball mill, pre-freeze for 10-20 minutes, and then operate at -196°C at an alternating frequency of 25-30 Hz for 5-6 minutes and 3-7 Hz for 2-3 minutes. After 7-9 cycles, lithium lanthanum powder with a micro-nano structure is obtained.

2. The method for preparing lithium lanthanum powder with micro-nano structure according to claim 1, characterized in that: In the step 1, polymethyl methacrylate accounts for 15% of the total mass of metallic lithium and lanthanum, octadecyl phosphoric acid accounts for 0.2%, and 2 mL of p-xylene is added to every 1000 mg of metallic lithium and lanthanum.

3. The method for preparing a lithium lanthanum powder with a micro-nano structure according to claim 2, characterized in that: The method also includes step three, filtering the lithium lanthanum powder using a 150-250 mesh sieve.

4. The method for preparing a lithium lanthanum powder with a micro-nano structure according to any one of claims 1 to 3, characterized in that: In the step 2, the weighed raw materials are placed in a frozen ball mill, with a ball-to-material ratio of 100:1, and a frozen ball mill is used. After pre-freezing for 15 minutes, the mill is operated at an alternating frequency of 30 Hz for 5 minutes and 5 Hz for 2 minutes, for 7 cycles.

5. Application of the lithium lanthanum powder with micro-nano structure according to claim 1 in lithium metal batteries.

6. The use of a lithium lanthanum powder with a micro-nano structure in a lithium metal battery according to claim 5, characterized in that: The lithium lanthanum powder was sieved through a 300-500 mesh 316 L stainless steel mesh sieve with a diameter of 8-12 mm and then loaded on the stainless steel mesh sieve to prepare an electrode sheet.

Citation Information

Patent Citations

  • A passivated lithium powder and its preparation method, a positive electrode material with the passivated lithium powder added, and a battery.

    CN105762328B

  • Modified lithium-free negative electrode, preparation method thereof and lithium ion battery with modified lithium-free negative electrode

    CN109309194A

  • Micro-nano LiSr alloy composite material as well as preparation method and application thereof

    CN117701928A